PESAN DAKWAH PADA FILM 172 DAYS KARYA NADZIRA SHAFA (ANALISIS SEMIOTIKA PERSPEKTIF ROLAND BARTHES) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
The results showed that the form of da'wah message produced was the call to pray, the wearing of headscarves and clothing such as robes (gamis) specifically for men when going to pray, the process of ta'aruf, which is interpreted as not allowed to date, not cutting off the relationship between friends and relatives even though they are married, and the karma of a wife to her husband, namely by kissing her husband's hand when he is about to travel in order to get sustenance. Then the representation of the da'wah message contained in the 172 Days film is the existence of spiritual awareness, moral teaching, self-development, relationships with others, struggle and fortitude, family values and brotherhood, and responsibility and trust.The method used in analyzing the da'wah message in the 172 Days film is by selecting 5 (five) scenes from 87 scenes contained in the 172 Days film, namely scenes 1, 14, 26, 29, and 32. Implications The results of this study can contribute scientific thoughts and ideas, as well as enrich the treasure trove of knowledge about semiotic analysis.The existence of this research can be a trigger for the presence of similar research by collaborating communication science with studies on da'wah science. In the context of the object of research, namely drama movie shows, it is hoped that it will be able to open a broader understanding of mass media and the problems that surround it. The results of this study can contribute scientific thoughts and ideas, as well as enrich the treasure trove of knowledge about semiotic analysis.